Strategi Komunikasi Pemasaran Sanggar Gema Asyura di Media Sosial Instagram Menggunakan Pendekatan AIDA - Hesti Apriliani; Riswanto (Jurnal MADIA (Jurnal Humas dan Media Kontemporer), 2026)
This study aims to examine the marketing communication of Sanggar Gema Asyura through its Instagram account @gemaasyura2020. Sanggar Gema Asyura is a cultural arts group in Bengkulu City that specializes in traditional dance and dol music and has achieved national recognition. However, its digital presence on Instagram remains limited, with only about 259 followers and inconsistent posting activity. The study employs a descriptive qualitative approach, utilizing data collection techniques such as in-depth interviews with five informants, observation, and documentation. Analysis was conducted using Elias St. Elmo Lewis’s AIDA Theory (Attention, Interest , Desire , Action). The results indicate that all four stages of AIDA have been implemented with varying levels of effectiveness. Overall, the Desire and Action stages were more effective than the Attention and Interest stages. Inconsistent content management remains the primary obstacle to optimizing the studio’s digital marketing communication. Keywords: Art Studio, Gema Asyura, Instagram, Marketing Communications, Social Media.